ANALISIS PENGARUH FAKTOR FUNDAMENTAL INTERNAL DAN EKSTERNAL TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR PERBANKAN DI BURSA EFEK INDONESIA - Mohammad Aryo Arifin (Jurnal Media Wahana Ekonomika, 2012)
This study entitled "Analysis of Effect of Internal and External Factors Fundamental to the Company Stock Prices Stock Exchange Banking Sector in Indonesia". The purpose of this study was to analyze the factors that affect stock prices. Some factors that influence the price of shares carried out in this study is the operating profit, the systematic risk, interest rate of SBI, and inflation.Source of data used in this research is secondary data derived from the Indonesian stock exchange data consisting of annual financial reports and website of Bank Indonesia. The sample of companies used by 18 companies that issued Banking financial statements for the year 2005-2009. The method of analysis used in this research is descriptive analysis and multiple linear regression.The results of this study indicate that (1) partially, operating income had a positive influence on stock prices. Systematic risk had no effect on stock prices. SBI interest rate has no effect on stock prices, inflation negatively affect stock prices. (2) simultaneous independent variables (operating income, systematic risk, interest rate and inflation SBI) has a significant influence on stock prices. Keywords          : stock price, operating profit, the systematic risk, interest rate of SBI,  inflation